Existence for viscoplastic contact with Coulomb friction problems - Amina Amassad; Caroline Fabre (International Journal of Mathematics and Mathematical Sciences)
We present existence results in the study of nonlinear problem of frictional contact between an elastic-viscoplastic body and a rigid obstacle. We model the frictional contact both by a Tresca's friction law and a regularized Coulomb's law. We assume, in a first part, that the contact is bilateral and that no separation takes place. In a second part, we consider the Signorini unilateral contact conditions. Proofs are based on a time-discretization method, Banach and Schauder fixed point theorems.